A chemical proteomics approach for global mapping of functional lysines on cell surface of living cell - Wang, Ting; Ma, Shiyun; Ji, Guanghui; Wang, Guoli; Liu, Yang; Zhang, Lei; Zhang, Ying; Lu, Haojie (Nature communications, 2024)
Cell surface proteins are responsible for many crucial physiological roles, and they are also the major category of drug targets as the majority of therapeutics target membrane proteins on the surface of cells to alter cellular signaling. Despite its great significance, ligand discovery against membrane proteins has posed a great challenge mainly due to the special property of their natural habitat. Here, we design a new chemical proteomic probe OPA-S-S-alkyne that can efficiently and selectively target the lysines exposed on the cell surface and develop a chemical proteomics strategy for global analysis of surface functionality (GASF) in living cells. In total, we quantified 2639 cell surface lysines in Hela cell and several hundred residues with high reactivity were discovered, which represents the largest dataset of surface functional lysine sites to date. We discovered and validated that hyper-reactive lysine residues K382 on tyrosine kinase-like orphan receptor 2 (ROR2) and K285 on Endoglin (ENG/CD105) are at the protein interaction interface in co-crystal structures of protein complexes, emphasizing the broad potential functional consequences of cell surface lysines and GASF strategy is highly desirable for discovering new active and ligandable sites that can be functionally interrogated for drug discovery. Ligand discovery against membrane proteins has been a major challenge, mainly due to the peculiar nature of their natural habitat. Here, the authors designed a new chemical proteomic probe that targets the lysines exposed on the cell surface and developed a chemical proteomic strategy for global analysis of surface functionality in living cells.